2019
DOI: 10.3389/fimmu.2019.01916
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Gut Barrier Changes to Multiple Sclerosis Pathophysiology

Abstract: The gut barrier consists of several components, including the mucus layer, made of mucins and anti-bacterial molecule, the epithelial cells, connected by tight junction proteins, and a mixed population of cells involved in the interplay with microbes, such as M cells, elongations of “antigen presenting cells” dwelling the lamina propria, intraepithelial lymphocytes and Paneth cells secreting anti-bacterial peptides. Recently, the influence of intestinal permeability (IP) changes on organs far from gut has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 46 publications
(49 reference statements)
0
37
1
Order By: Relevance
“…Occludin is a structural and regulatory protein that modulates epithelial barrier function together with paracellular pore‐forming protein claudins 49 . Decreased expression in TJ proteins could disrupt TJ pores resulting in increased permeability to macromolecules and ions, which is linked to a variety of local and systemic diseases 49‐52 . The observation that application of IL‐6 increased paracellular permeability further confirmed the linkage of pro‐inflammatory cytokines and intestinal barrier dysfunction.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Occludin is a structural and regulatory protein that modulates epithelial barrier function together with paracellular pore‐forming protein claudins 49 . Decreased expression in TJ proteins could disrupt TJ pores resulting in increased permeability to macromolecules and ions, which is linked to a variety of local and systemic diseases 49‐52 . The observation that application of IL‐6 increased paracellular permeability further confirmed the linkage of pro‐inflammatory cytokines and intestinal barrier dysfunction.…”
Section: Discussionmentioning
confidence: 89%
“…49 Decreased expression in TJ proteins could disrupt TJ pores resulting in increased permeability to macromolecules and ions, which is linked to a variety of local and systemic diseases. [49][50][51][52] The observation that application of IL-6 in- in females. 60,61 It is noteworthy that IBS is commonly observed in military personnel exposed to combat conditions, a predominately male population.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in patients with multiple sclerosis have found increased abundance of mucosal bacteria including Akkermansia muciniphila, Methanobrevibacter, and Acinetobacter calcoaceticus and decreased abundance of Butyricimonas, Faecalibacterium, and Parabacteroides distasonis (Cantarel et al, 2015;Jangi et al, 2016;Berer et al, 2017;Cekanaviciute et al, 2017). Such alterations in the mucosal microbiome potentially favor the growth of pathogenic bacteria that alter the composition of the mucus layer and therefore may exacerbate core symptoms of these disorders (Camara-Lemarroy et al, 2018;Buscarinu et al, 2019) CONCLUSION In summary, multiple pathways relevant to mucus homeostasis may be impacted by nervous system impairments in neurological disease. Furthermore, altered mucus properties could contribute to the widespread observations of microbial dysbiosis in autism, Parkinson's Disease, Alzheimer's Disease, and multiple sclerosis, and potentially exacerbate core symptoms.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…COVID-19 may indeed trigger MS or its clinical manifestation also through other mechanisms. In MS, intestinal dysbiosis and changes in intestinal permeability are increasingly recognized as modulators of neuroinflammatory mechanisms through the so-called gut–brain axis [ 57 ]. Therefore, the alteration of the intestinal barrier and microbiota induced by SARS-CoV2 may enhance autoreactive response (as previously mentioned).…”
Section: Multiple Sclerosismentioning
confidence: 99%